Indonesia-English Code Mixing Found in Glad2glow’s Instagram Posts - Pande Dwi Vala Mantika; I komang sulatra (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
Abstract This research explores the presence of code mixing in Instagram captions posted by the Indonesian skincare brand Glad2Glow. The main objective is to identify the different types of code mixing used and understand the reasons behind their application in the brand’s marketing content. Utilizing Hoffman’s (1991) theory as the foundation for analysis, the study adopts a descriptive qualitative approach. The data were gathered through an observation method, specifically by taking notes on captions uploaded to Glad2Glow’s official Instagram account between January 4th and May 31st, 2025. The findings indicate that all three types of code mixing intra-sentential, intra-lexical, and phonological are present in the data. Among these, intra-sentential code mixing appears most frequently, while phonological mixing is the least common. The most common reason for using code mixing is to talk about particular topics, especially skincare related terms that are more familiar and appealing when expressed in English. Additionally, code mixing is used to express group identity and emphasize promotional messages in a more persuasive and relatable manner. These results suggest that code mixing functions as a strategic linguistic tool in digital branding to connect with bilingual audiences and enhance brand engagement.